Representations for the generalized inverses of a modified operator - Mosić, D. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Some explicit representations for the generalized inverses of a modified operator $A + YGZ$ are derived under some conditions, where $A, Y, Z$, and $G$ are operators between Banach spaces. These results generalize the recent works aboutthe Drazin inverse and the Moore – Penrose inverse of complex matrices and Hilbert-space operators.